Legal Hierarchy and Access to Justice in Cooperative Bankruptcy Law: Reassessing SEMA No. 1/2022 - Dewi Iryani; Binar Jon Vic S (PT. Global Research Collaboration, 2026)
This study examines whether Supreme Court Circular Letter (SEMA) No. 1/2022, which restricts bankruptcy petition authority against cooperatives exclusively to the Minister of Cooperatives and SMEs, is compatible with Law No. 37/2004 on Bankruptcy and Law No. 25/1992 on Cooperatives through legal hierarchy theory and access to justice principles. Method: Using statutory, conceptual, and case-based approaches, this normative legal research analyzes constitutional provisions, statutes, court decisions, and comparative frameworks from Germany and the Netherlands. Findings: The findings demonstrate that SEMA No. 1/2022 constitutes an ultra vires action violating the lex superior derogat legi inferiori principle by creating substantive norms contradicting Article 2(1) of the Bankruptcy Law. The restriction diminishes creditors’ constitutional right to access justice under Article 28D (1) of the 1945 Constitution while creating conflicts of interest in ministerial authority. PKPU (Penundaan Kewajiban Pembayaran Utang or Suspension of Debt Payment Obligations) petition authority is similarly affected. Comparative analysis reveals that Germany and the Netherlands maintain creditor standing while implementing procedural modifications protecting cooperative interests. Conclusion: This study proposes a Parallel Authority Model preserving creditor standing while enabling ministerial participation through notification and intervention mechanisms.